Analisa Perbandingan Performansi Hot Standby Router Protocol (HSRP) dengan Gateway Load Balancing Protocol (GLBP) Pada Router Spoke DMVPN - Claudia, Michelle; Rifqi, Muhammad (STMIK Budi Darma, 2021)
The use of internet connections to develop Virtual Private Network (VPN) lines in companies has been massively applied. An example is the use of Dynamic Multipoint VPN (DMVPN) technology from Cisco, which can connect Spoke or branch offices through HUB or data centers. Besides requiring a secure network, companies also need high network availability. One of them is by using the redundancy method in order to minimize downtime when device damage occurs. In this research, the spoke router will apply two redundancy methods by Cisco, which are Hot Standby Router Protocol (HSRP) and Gateway Load Balancing (GLBP). This research aims to compare the QoS performances and downtime between the two protocols in order to discover the suitable method for DMVPN networks at branch offices. The test scenario is conducted on the GNS-3 simulator using the File Trasnfer Protocol (FTP) service. The obtained test result shows that the HSRP throughput value is smaller from the GLBP with a difference of 0.20%, the increase in the average delay of the HSRP is smaller from the GLBP with a difference of 1.07%. The HSRP data transfer time is faster than GLBP with a difference of 1.49%, and HSRP downtime is 4.13% faster than GLBP. The conclusion is that a suitable redundancy solution for spoke router using the HSRP method